Histopathology of organs of grass carp (Ctenopharyngodon idella) from the Ile river and the Kapshagay reservoir (Eurasian Journal of Ecology, 2022)
The ecosystems of the Ile-Balkhash region have been subjected to anthropogenic pressure in recent years, which leads to a decrease in biodiversity, including commercial fish. In the present study, using the method of atomic absorption spectroscopy, the content of heavy metals in the surface waters and bottom sediments of the Ile River (upper reach, Panfilovsky district, Almaty region) and the southeastern part of the Kapshagay reservoir was determined. An excess of MPC among the 9 determined HMs, was found for Fe > Zn > Pb > Cd. The accumulation of these HMs was also found in organs (gills, liver, large intestine, kidneys) of grass carp caught in different parts of the studied water bodies. With the help of histological and morphometric methods, the morpho-functional state of grass carp was assessed and destructive changes in the same organs were revealed. At the same time, it was found that the nature and quantitative indicators of histopathological changes depend on the level of HM accumulation and the place of capture. At the same time, the greatest structural changes were found in the organs of grass carp from the Ile River (upper reach) compared with fishes from the southeastern part of the Kapshagay reservoir. In the gills, hyperplasia, fusion of the plates, necrosis and edema of the gill epithelium were revealed. Expansion of spaces of Disse, sinusoids, dystrophy and necrosis of hepatocytes, numerous melanomacrophage accumulations were found in the liver. In the large intestine – stratification of wall tissues: muscular, serous, submucosal and mucous bases, necrosis of enterocytes. In the kidneys, wrinkling and divergence of capillaries in the vascular glomeruli, an increase in the Bowman space, dystrophic and necrobiotic changes in the epitheliocytes of the proximal and distal renal tubules were observed. It was concluded that heavy metals bioaccumulated in the tissues and organs of grass carp subsequently worsen their histopathological state and, thus, affect the health of fish. The revealed histopathological effects can be biomarkers of the state of the aquatic environment.Key words: Ile river, Kapshagay reservoir, heavy metals, grass carp, histopathology.